Ensuring the efficiency of production costs the role and importance of innovations - Berdinazarov Zafar Ulashovich; Nargiza Eshkobilova Mengnorovna (Genius Journals, 2023)
In the conditions of globalization in the world economic system, the current of scientific research on efficient use of costs in production has increased. One of the factors of reducing costs in production is the use of innovative technologies. It should be noted that the process of using "Industry 4.0" technology is currently underway in most of the developing countries. This article talks about the urgency of using innovative technologies in the industrial enterprises of Uzbekistan and the importance of using innovative technologies in product production
Keywords: Innovation; economy; Industry; additive technologies